2013
DOI: 10.1002/jbm.a.34911
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐rich coating promotes binding of proteins and endothelialization of polyethylene terephthalate polymers

Abstract: The formation of endothelial cell monolayer on prosthetic implants has not sufficiently explored. The main reasons leading to the development of thrombosis and/or intimal hyperplasia is the lack of endothelialization. In the present work, we have studied the influence of oxygen and fluorine plasma treatment of polyethylene terephthalate (PET) polymers on human microvascular endothelial cell adhesion and proliferation. We characterized the polymer surface, wettability, and oxidation potential upon plasma treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Oxygen is the most commonly used for plasma treatment of the surface to improve the wettability and controlling of the biocompatibility. It has been shown that the cell proliferation increased by 30% when HEMC-1 cultured on oxygen plasma-treated polymers after 48 h [59]. Oxygen plasma-treated samples could enhance not only the cell adhesion and proliferation, but also the protein adhesion [38].…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen is the most commonly used for plasma treatment of the surface to improve the wettability and controlling of the biocompatibility. It has been shown that the cell proliferation increased by 30% when HEMC-1 cultured on oxygen plasma-treated polymers after 48 h [59]. Oxygen plasma-treated samples could enhance not only the cell adhesion and proliferation, but also the protein adhesion [38].…”
Section: Discussionmentioning
confidence: 99%
“…for endothelialisation). 25 However, use of plasma treatment alone may not be enough, 26 especially as there may be a more subtle role that is played by surface topography. This suggests that a synergistic role may be played by incorporating both treatment approaches, as has been suggested by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was explained by the creation of new functional groups and the modification of surface morphology, which promotes the adhesion of endothelial cells. Numerous studies have proved that plasma treatment significantly improves biocompatible properties of polymer materials [17,45,46,47,48,49,50]. In their study, Jaganjac et al [49] proved that oxygen rich coating after plasma treatment promotes binding of proteins and endothelialization of polyethylene terephthalate polymer.…”
Section: Biomaterialsmentioning
confidence: 99%
“…Numerous studies have proved that plasma treatment significantly improves biocompatible properties of polymer materials [17,45,46,47,48,49,50]. In their study, Jaganjac et al [49] proved that oxygen rich coating after plasma treatment promotes binding of proteins and endothelialization of polyethylene terephthalate polymer. In another study it was shown that cells prefer to adhere on moderate hydrophobic polymer surfaces, rather than on hydrophilic or super-hydrophilic ones.…”
Section: Biomaterialsmentioning
confidence: 99%